Advancing knowledge of gas migration and fugitive gas from energy wells in northeast British Columbia, Canada. Issue 2 (23rd February 2019) - Cahill, Aaron G.; Beckie, Roger; Ladd, Bethany; Sandl, Elyse; Goetz, Maximillian; Chao, Jessie; Soares, Julia; Manning, Cara; Chopra, Chitra; Finke, Niko; Hawthorne, Iain; Black, Andrew; et al.
Abstract: Petroleum resource development is creating a global legacy of active and inactive onshore energy wells. Unfortunately, a portion of these wells will exhibit gas migration (GM), releasing fugitive gas (FG) into adjacent geologic formations and overlying soils. Once mobilized, FG may traverse the critical zone, impact groundwater, and emit to the atmosphere, contributing to greenhouse‐gas emissions. Understanding of GM and FG has increased in recent years but significant gaps persist in knowledge of (1) the incidence and causes of GM, (2) subsurface baseline conditions in regions of development required to delineate GM and FG, and (3) the migration, impacts, and fate of FG. Here we provide an overview of these knowledge gaps as well as the occurrence of GM and FG as currently understood in British Columbia (BC), Canada, a petroleum‐producing region hosting significant reserves. To address the identified knowledge gaps within BC, the Energy and Environment Research Initiative (EERI) at the University of British Columbia is implementing several field‐focused research projects including: (1) statistical analyses of regulatory data to elucidate the incidence and causes of GM, (2) characterization of regional hydrogeology and shallow subsurface conditions in the Peace Region of the Montney resource play, and (3) investigation of the migration, impacts, and fate of FG in the shallow subsurface through controlled natural‐gas release. Together, the EERI investigations will advance understanding of GM and FG, provide scientific data that can inform regulations, and aid development of effective monitoring and detection methodologies for BC and beyond. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.